2018
DOI: 10.5114/ceh.2018.73155
|View full text |Cite
|
Sign up to set email alerts
|

The influence of NAFLD on the risk of atherosclerosis and cardiovascular diseases

Abstract: Non-alcoholic fatty liver disease (NAFLD) is the most common chronic liver disease in developed countries and is associated with obesity, dyslipidaemia, diabetes, and metabolic syndrome. Atherosclerosis and cardiovascular diseases are also highly prevalent in this group of patients, due to the presence of shared risk factors. The incidences of coronary artery calcification, hypertension, aortic valve sclerosis, diastolic dysfunction, atherosclerotic plaques, and increased carotid intima-media thickness were mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
45
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 66 publications
(49 citation statements)
references
References 69 publications
2
45
0
2
Order By: Relevance
“…Associations between NAFLD and atherosclerosis have been reported in several large epidemiology studies [3,20,21]. However, few studies have investigated whether the two diseases share any common pathophysiological mechanisms, which would suggest that they may respond to the same therapy.…”
Section: Discussionmentioning
confidence: 99%
“…Associations between NAFLD and atherosclerosis have been reported in several large epidemiology studies [3,20,21]. However, few studies have investigated whether the two diseases share any common pathophysiological mechanisms, which would suggest that they may respond to the same therapy.…”
Section: Discussionmentioning
confidence: 99%
“…The occurrence rate of coronary artery disease (CAD) increased 4.7 times in the adult NAFLD population and the severity of CAD was also signi cantly associated with the presence of NAFLD [6]. Multiple factors contribute to the pathogenesis of NAFLD and CAD [7]. Accumulated evidence suggested that gene polymorphism is an important risk factor not only for the occurrence of NAFLD or CAD in the general population, but also for the occurrence of CAD in the NAFLD patients [3,8].…”
Section: Introductionmentioning
confidence: 99%
“…NAFLD is an independent risk factor for type 2 diabetes and cardiovascular disease, and emerging evidence suggests that NAFLD may influence bone density in adults, since the liver produces factors that affect bone health . Previous evidence also suggests that more severe liver disease in NAFLD may be associated with more pronounced reductions in bone density, since a recent study of 231 adult patients with NAFLD showed that liver fibrosis (assessed by transient elastography) was independently associated with low bone mineral density (BMD) .…”
Section: Introductionmentioning
confidence: 99%